Unresolved ethical issues of genetic counseling and testing in clinical psychiatry - Perry, Julia; Bunnik, Eline; Rietschel, Marcella; Bentzen, Heidi Beate; Ingvoldstad Malmgren, Charlotta; Pawlak, Joanna; Chaumette, Boris; Tammimies, Kristiina; Bialy, Filip; Bizzarri, Virginia; Borg, Isabella; Coviello, Domenico; et al. (Psychiatric genetics, 2025)
Objective - This position article discusses current major ethical and social issues related to genetic counseling and testing in clinical psychiatry (PsyGCT). - Methods - To address these complex issues in the context of clinical psychiatry relevant to PsyGCT, the interdisciplinary and pan-European expert Network EnGagE (Enhancing Psychiatric Genetic Counseling, Testing, and Training in Europe; CA17130) was established in 2018. We conducted an interdisciplinary, international workshop at which we identified gaps across European healthcare services and research in PsyGCT; the workshop output was summarized and systematized for this position article. - Results - Four main unresolved ethical topics were identified as most relevant for the implementation of PsyGCT: (1) the problematic dualism between somatic and psychiatric disorders, (2) the impact of genetic testing on stigma, (3) fulfilling professional responsibilities, and (4) ethical issues in public health services. We provide basic recommendations to inform psychiatrists and other healthcare professionals involved in the clinical implementation of PsyGCT and conclude by pointing to avenues of future ethics research in PsyGCT. - Conclusion - This article draws attention to a set of unresolved ethical issues relevant for mental health professionals, professionals within clinical genetics, patients and their family members, and society as a whole and stresses the need for more interdisciplinary exchange to define standards in psychiatric counseling as well as in public communication. The use of PsyGCT may, in the future, expand and include genetic testing for additional psychiatric diagnoses. We advocate the development of pan-European ethical standards addressing the four identified areas of ethical-practical relevance in PsyGCT.